Cerebellar cognitive disorder parallels cerebellar motor symptoms in Friedreich ataxia. Issue 6 (8th June 2020) - Naeije, Gilles; Rai, Myriam; Allaerts, Nick; Sjogard, Martin; De Tiège, Xavier; Pandolfo, Massimo
Abstract: Dentate nuclei (DN) are involved in cerebellar modulation of motor and cognitive functions, whose impairment causes ataxia and cerebellar cognitive affective syndrome (CCAS). Friedreich ataxia (FRDA) disease progression relates to degeneration of the dentate nucleus and dentato‐thalamic pathways, causing cerebellar ataxia. Volumetric MRI also shows mild loss in the cerebellar cortex, brainstem, and motor cortex. Cognitive deficits occur in FRDA, but their relationship with ataxia progression is not fully characterized. We found a significant positive correlation between severity of patients' ataxia and more marked CCAS as assessed with the CCAS‐Scale. This relation could be related to progressive DN impairment.